2016
DOI: 10.1111/pde.12873
|View full text |Cite
|
Sign up to set email alerts
|

Contact Sensitization in Children: A Retrospective Study of 2,614 Children from a Single Center

Abstract: Contact sensitization is quite common in young children. This study adds some information on the most common contact allergens. A similar prevalence of positive patch test reactions was found in children with and without AD, but children with AD had a greater prevalence of positive patch test reactions to potassium dichromate, Compositae mix, and disperse blue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
44
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 26 publications
8
44
2
1
Order By: Relevance
“…As the presence of these surfactants is frequent in daily cosmetic products (shampoo, liquid soap, toothpaste), sensitization to the agents could easily occur. High prevalences of CAPB/DMAPA contact allergies have been found by other authors as well, but are underreported as they are often not tested, as they are not in the EBS and only tested on indication 25, 48, 49. The allergenic potential of CAPB has been disputed, and it is argued whether CAPD is a true allergen or only an irritant 50.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…As the presence of these surfactants is frequent in daily cosmetic products (shampoo, liquid soap, toothpaste), sensitization to the agents could easily occur. High prevalences of CAPB/DMAPA contact allergies have been found by other authors as well, but are underreported as they are often not tested, as they are not in the EBS and only tested on indication 25, 48, 49. The allergenic potential of CAPB has been disputed, and it is argued whether CAPD is a true allergen or only an irritant 50.…”
Section: Discussionmentioning
confidence: 96%
“…A large multicentre study in Dutch children showed that children with AD were significantly more often sensitized to fragrances and wool alcohols 21. Also, potassium dichromate, disperse blue 106 and compositae mix are frequent sensitizers 25. If corticosteroid therapy is not sufficient for treating AD anymore, many dermatologists may suspect an allergy for corticosteroids 24, 26, 27…”
Section: Introductionmentioning
confidence: 99%
“…Cobalt was the second most common allergen. Authors of recent studies on allergic contact dermatitis in children have reported similar high frequencies of positive patch test reactions to this allergen . Cobalt allergy is currently a “hot topic”, as it is increasingly being recognized as an independent sensitizer, and new sources of exposure have to come to light .…”
Section: Discussionmentioning
confidence: 97%
“…33,34 In the present study, the overall sensitization prevalence was the same among children with atopic dermatitis as among children without atopic dermatitis, in agreement with recent similar studies. 5,35,36 However, there is an inherent risk of selection bias in retrospective studies of patients referred for patch testing: As children were patch tested because of either recalcitrant eczema or a clinical suspicion of allergic contact dermatitis, it could be that children without atopic dermatitis were more carefully selected for patch testing, that is, there was a strong suspicion of allergic contact dermatitis, whereas children with atopic dermatitis may be referred for patch testing because of aggravation of the atopic dermatitis. This could lead to an underestimation of the prevalence of contact allergy among children with atopic dermatitis.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of positive reactions is typically lower than that seen with Compositae mix 6% pet. : the mean prevalence of positive reactions in a multicentre study of 2818 Swedish patients was 1.1%, and, likewise, an Italian study of 2614 children aged <11 years old reported a prevalence of positive reactions of 1.6%. Compositae mix 5% pet.…”
Section: Discussionmentioning
confidence: 99%